The degree of availability of professional digital skills in the performance of faculty members at The University of Hail From their point of view - Samara, Hatouf Farah; Alhaj, Ahlam Ibrahim Mohammed; Suliman, Ghada Alameen Ahmed; Yousif, Ahlam Elimam Abdalla (Journal of Educational and Psychological Sciences, 2023)
The study aimed to investigate the degree of availability of professional digital skills in the performance of faculty members at the University of Hail. The study followed the descriptive approach, by applying a questionnaire consisting of (50) items distributed on four axes. The study sample consisted of (109) faculty members at the University of Hail. During the year 2022/2023, they were selected using a random stratified method. The results of the study showed that the degree of availability of professional digital skills in the performance of faculty members at the University of Hail is very high on the total score, with an arithmetic mean of (4.34) and a percentage of (86.4%). Results Availability of professional digital skills in the performance of faculty members to a very large extent on each axis of professional digital skills. The axis of planning skills for university teaching ranked first, with an arithmetic mean of (4.39), and with a percentage of (87.8%). The axis of planning skills came in the second rank. University teaching implementation skills, with an arithmetic mean of (4.38), with a percentage of (87.6%), and the third rank came in the axis of university teaching skills evaluation skills, with an arithmetic mean of (4.27), and with a percentage of (85.4%), and the fourth rank came in the axis of university situation management skills. and with an arithmetic mean of (4.24), with a percentage of (84.8%), the results also showed that there was a statistically significant difference in the degree of availability of professional digital skills in the performance of faculty members due to the variable number of digital training courses, and in favor of (4) courses or more, while it did not appear Statistically significant difference due to the variable of college or teaching experience. In light of the results of the study, a number of recommendations were presented, the most important of which is spreading digital culture among faculty members and encouraging them to improve their competencies and develop them to keep pace with the increasing digital developments day after day to improve the educational environment and keep pace with the global development in the field of technology.